Influence of fermentative modification of rice flour starch on bread quality for patients with celiac disease - Medvid, Irina; Shydlovska, Olena; Dotsenko, Viktor (My University, 2017)
The expedient use of ferments with amylolytic activity for carbohydrate composition modification of rice flour aiming to improve the quality of gluten-free bread is scientifically based. Hydrolyzation of rice flour starch with the help of amylolytic ferments in preparation of a bread for patients suffering from celiac disease helps to intensify microbiological processes in the dough, to improve quality scores of ready-made products and prolonging of their expiration date.
Keywords: glucoamylase; целіакія; глюкоамілаза; rice flour; rice starch; рисове борошно; крохмаль рисовий; кафедра готельно-ресторанної справи